Implementation of the Merah Putih Cooperative Policy to Improve Community Economy in East Kotawaringin Regency - Risa Gunanti; Zainal Fatah; Eny Haryati; Kristyan Dwijosusilo (International Journal of Social Science and Humanity, 2026)
This study aims to analyze the implementation of the Merah Putih Cooperative policy in developing the community economy in East Kotawaringin Regency. This study uses a qualitative approach and is included in the descriptive research category. Data were obtained through observation, interviews, and documentation involving the local government, village government, cooperative administrators, and the community as research informants. The research findings indicate that the implementation of the Merah Putih Cooperative policy has been carried out through socialization activities, the establishment of cooperative institutional structures, and mentoring from the local government to the village government and community. Cooperatives have a positive influence on community economic growth, particularly in facilitating access to business capital, expanding the market for local products, and increasing community involvement in village economic activities. However, policy implementation still faces various challenges, such as a lack of human resources, limited community understanding of cooperatives, and limited capital and facilities to support cooperatives. Elements supporting policy implementation include support from the local government, community involvement, and the village economic potential that can be enhanced through cooperatives. Therefore, capacity building of cooperative institutions and continuous mentoring are needed so that cooperatives can grow independently and sustainably in improving the welfare of village communities.